A transconductance-enhancement cascode Miller compensation for low-power multistage amplifiers. (March 2018) - Dong, Siwan; Zhu, Zhangming
Abstract: A transconductance-enhancement cascode Miller compensation technique is proposed for low supply-power, large or very large capacitive load multistage amplifiers. By using the transconductance-enhancement operational amplifiers and the local impedance attenuation network, both the gain bandwidth and setting time are thus significantly improved. The effectiveness of the method has been verified in a 0.18 μm CMOS process, the proposed three-stage amplifier has over 100 dB gain, 6.5 MHz gain-bandwidth product, and 0.83 V/μs slew rate while consuming 23 μW power from a 1.2 V supply while driving a 560 pF load.